Assessment on the Effect of Pre-During-Post COVID-19 on the Profitability of the Selected Food Manufacturers in the Philippines - Agote, Jennifer D., Asprec, Herschel Kiersten O., Baltazar, Faye Angelica R., Barroga, Alexandra Louise N., Cancino, Giox Honorei M., Siggayo, Pamela Andrea D. 4 0 16; 5 (2023)
Abstract This study focused on assessing the effect of the COVID -19 Pandemic on the profitability performance in relation to tangible assets of selected food manufacturers in the Philippines. This aims in identifying whether firms were able to maintain a prospect of gaining profits and were able to generate a return on assets (ROA) during the Pre, During, and Post Pandemic. The researchers gather their data from the provided Annual Financial Statement of Monde Nissin, Universal Robina Corporation, Alliance Global Group, Del Monte Food Corporation, and Ginebra San Miguel Corporation through its website as a scope of the study. Keywords: Profitability, Manufacturer, Pandemic.
Research paper: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2